Investigation of the impact of threshold pressure gradient on gas production from hydrate deposits. (1st July 2022) - Lu, Cheng; Qin, Xuwen; Ma, Chao; Yu, Lu; Geng, Lantao; Bian, Hang; Zhang, Keni; Zhou, Yingfang
Highlights: The TPG and the permeability-viscosity ratio agree well with a power law function. The TPG plays a critical role in gas production from hydrate-bearing sediments with unconsolidated argillaceous siltstones. A small TPG can effectively expand the gas output, which can expand the three-phase coexisting area. When the production well does not completely drill out the hydrate layer, the bottom water invasion would appear. The TPG can restrict the aquifer invading into hydrate layer. Abstract: Many hydrate-bearing sediments are featured with unconsolidated argillaceous siltstones, which exist the non-Newtonian flow and threshold pressure gradient due to the high content of clay. In this study, the threshold pressure gradient of hydrate reservoir in the South China Sea is experimentally clarified. The quantitative relationship between it and the reservoir parameters is established. The function of threshold pressure gradient has been added into TOUGH + HYDRATE simulator. Here, site SH2, a candidate for field testing comprising a clayey silt gas hydrate reservoir in the Shenhu area of the South China Sea, was chosen to investigate the effect of threshold pressure gradient on gas production behavior through numerical simulations. The simulation results show that threshold pressure gradient has a significant impact on gas extraction. When the experimental value was applied, the gas production was enhanced unexpectedly, where cumulative gas output doubled in 5 years. The active hydrate dissociating area (gas, water and hydrate coexist) has notably extended, accompanying with the expanding cool zone. Water blockage near well was relieved. However, with the increasing of threshold pressure gradient, propagation of pressure would be restrained seriously. The pressure and hydrate of far-field formations stay "frozen". The bottom water invasion was weakened.